The Association between Perceived Stress, Quality of Life, and Level of Physical Activity in Public School Teachers - da Silva, Claudiele Carla Marques [UNESP]; Santos, Amanda Barbosa dos [UNESP]; Leoci, Isabella Cristina [UNESP]; Leite, Enrique Gervasoni [UNESP]; Antunes, Ewerton Pegorelli [UNESP]; Torres, Wesley [UNESP]; Mesquita, Eduardo Duarte de Lima [UNESP]; Delfino, Leandro Dragueta [UNESP]; Beretta, Victor Spiandor [UNESP] (MDPI, 2024)
Chronic high stress levels related to work impact the quality of life (QoL). Although physical activity improves QoL, it is not clear whether this life study habit could attenuate possible relationships between QoL and stress in public school teachers. The sample for this study was made up of 231 teachers from public schools. QoL was assessed using the Short-Form Health Survey and physical activity via Baecke’s questionnaire. A Likert scale assessed stress level perception. Poisson Regression analyzed the association between stress level and QoL domains adjusted for sex, age, and socioeconomic conditions (model 1). In model 2, physical activity level was inserted in addition to model 1. Seven out of eight domains of QoL, except the domain of pain, were associated with high levels of stress (all p < 0.05–model 1). However, in model 2, the associations of the high levels of stress with general health status (p = 0.052) and functional capacity (p = 0.081) domains of QoL were mitigated. Our results indicated that physical activity mitigated the relationship between higher levels of stress and lower perception of general health status and functional capacity domains in secondary public school teachers.
Keywords: physical activity; teaching; workload